Are emotionally driven and addictive-like eating behaviors the missing links between psychological distress and greater body weight?. (1st January 2018) - Bourdier, L.; Orri, M.; Carre, A.; Gearhardt, A.N.; Romo, L.; Dantzer, C.; Berthoz, S.
Abstract: There is now a large body of evidence suggesting a significant association between emotional discomfort management, disordered eating behaviors and weight status. In the field of overweight and obesity, emotionally driven eating habits that resemble addictive behaviors are considered as a risk factor. This study aimed to investigate in a large sample of French university students 1) the associations between self-reported levels of psychological distress (PD), emotional eating (EE), food addiction (FA) and Body Mass Index (BMI); and 2) the potential mediation effect of eating behaviors (EE and FA) between PD and BMI. The responses of 1051 students (76.3% females) to self-reports assessing PD (Perceived Stress Scale, Hospital Anxiety and Depression Scale), EE (Intuitive Eating Scale-2) and FA (modified Yale Food Addiction Scale) were analysed. Associations between variables (Spearman correlation) and group comparisons by sex and BMI categories (Student's t tests/ANOVA) were tested, followed by Structural Equation Modeling (SEM) by sex. Among females and males, EE and FA scores were positively inter-related and correlated with PD scores and BMI. Moreover, among females and males, SEM showed that both EE and FA acts as mediators between PD and BMI. Hence, among educated young adults, using food consumption for down-regulating negative mood places the individual at risk for overweight and obesity. This study further emphasizes the necessity to take into account emotionally driven and addictive-like eating behaviors in interventions for promoting healthy eating and weight management.